Cigarette smoking behaviors and nicotine dependence at the intersection of sexual identity and sex in the United States: Findings from the National Survey on Drug Use and Health - Ganz, Ollie; Schulz, Jonathan A.; Ehlke, Sarah J.; King Jensen, Jessica L.; Villanti, Andrea C. (Preventive medicine reports, 2024)
Introduction: Cigarette smoking is disproportionately high among lesbian, gay, and bisexual (LGB) adults. Yet, collapsing these identities into a monolith can disguise important within group disparities (e.g., lesbian/gay versus bisexual female). The purpose of this study is to report recent national prevalence estimates and trends of cigarette smoking behaviors and nicotine dependence by sexual identity and sex. Methods: Data were from the 2015–2019 National Survey on Drug Use and Health (n = 210,392; adults 18+), a nationally representative, repeated cross-sectional study of substance use and mental health in the U.S. We examined bivariate and multivariable associations between sexual identity and cigarette smoking measures (i.e., former smoking, lifetime smoking, current smoking, current daily smoking, nicotine dependence) by sex. We also examined linear time trends in current and former smoking. Covariates included age, race/ethnicity, education, annual household income, and survey year. Results: Bisexual women had the highest unadjusted prevalence of current smoking (31 %) and lowest of former smoking (25 %). LGB females and males had higher adjusted prevalence of current smoking, daily smoking, and nicotine dependence than heterosexual adults. Bisexual females and gay and bisexual males had lower adjusted prevalence of former smoking (adjusted prevalence ratio range: 0.78–0.85) than heterosexual counterparts. Discussion: This is the first study to identify disproportionately low prevalence of former smoking among bisexual females. Paired with findings of high prevalence of current cigarette smoking and nicotine dependence, these data suggest that tobacco control interventions targeted toward bisexual females are urgently needed to reduce the burden of cigarette smoking among these individuals.